Land value tax in the context of sustainable urban development and assessment. Part I ‐ policy analysis and conceptual model for the taxation system on real property - Raslanas, Saulius; Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras (International Journal of Strategic Property Management, 2010)
This article on issues related to real property taxes has two parts. Part One deliberates the concept of sustainable development as well as Lithuania’s real property taxation system and possible ways to improve it. Part Two analyses various methods of land assessment. The objectives of this paper are to analyze the importance of a tax on real property within the taxation system of Lithuania and to plan the implementation of such a reform in the future. A tax on land is presented as one alternative for a reform of the taxation system on real property in Lithuania. First Publish Online: 18 Oct 2010